2016
DOI: 10.1159/000447834
|View full text |Cite
|
Sign up to set email alerts
|

LEFTYA Activates the Epithelial Na+ Channel (ENaC) in Endometrial Cells via Serum and Glucocorticoid Inducible Kinase SGK1

Abstract: Background: Serum & glucocorticoid inducible kinase (SGK1) regulates several ion channels, including amiloride sensitive epithelial Na+ channel (ENaC). SGK1 and ENaC in the luminal endometrium epithelium, are critically involved in embryo implantation, although little is known about their regulation. The present study explored whether SGK1 and ENaC are modulated by LEFTYA, a negative regulator of uterine receptivity. Methods: Expression levels were determined by qRT-PCR and Western blotting, ENaC ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The epithelial sodium channel (ENaC) is required for uterine decidualization and embryo implantation (35). Serum and glucocorticoid-induced kinase-1 (SGK1) is a potent regulator of ENaC (37)(38)(39), and can up-regulate ENaC and increase ENaC membrane abundance (40) and activity (41,42). It was reported that 17b-estradiol could stimulate SGK1 mRNA and protein expression through ERb (estrogen receptor b) in the endometrial tissues of endometriosis patients (43).…”
mentioning
confidence: 99%
“…The epithelial sodium channel (ENaC) is required for uterine decidualization and embryo implantation (35). Serum and glucocorticoid-induced kinase-1 (SGK1) is a potent regulator of ENaC (37)(38)(39), and can up-regulate ENaC and increase ENaC membrane abundance (40) and activity (41,42). It was reported that 17b-estradiol could stimulate SGK1 mRNA and protein expression through ERb (estrogen receptor b) in the endometrial tissues of endometriosis patients (43).…”
mentioning
confidence: 99%
“…Detection of gene expression was performed with KapaFast-SYBRGreen (#KAPBKK4606, Peqlab VWR, Germany) and quantitative RT-PCR was performed on a BioRad iCycler iQ ™ Real-Time PCR Detection System (Bio-Rad Laboratories, Germany) as described earlier [ 30 ]. The expression levels of the samples were calculated by the 2 -ΔΔ Ct method using L19 to normalize for variances in input cDNA and expressed as arbitrary units.…”
Section: Methodsmentioning
confidence: 99%
“…The RMS cell lines were treated with the SGK1 inhibitor EMD638683 (APExBIO, Houston, Texas, USA, IC50 3µM) in the absence and presence of doxorubicin for the indicated periods and with the indicated concentrations. The concentration of EMD638683 has previously been shown to be effective [20, 33, 34]. …”
Section: Methodsmentioning
confidence: 99%